2011
DOI: 10.1590/s1516-35982011000600023
|View full text |Cite
|
Sign up to set email alerts
|

Use of cactus pear (Opuntia ficus indica Mill) replacing corn on carcass characteristics and non-carcass components in Santa Inês lambs

Abstract: -The objective of this study was to evaluate the biometric and morphometric measures, regional composition, carcass characteristics and non-carcass components of Santa Inês lambs submitted to levels of corn replaced by cactus pear in the diet. It was used 45 Santa Ines non-castrated male lambs, with average initial live weight of 25.50 ± 0.48 kg as a completely randomized block design with five treatments (0; 25; 50; 70 and 100%) and nine replicates. There was an effect of the diet on slaughter weight, empty b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
5
1
1
Order By: Relevance
“…Lambs receiving spineless cactus combined with Tifton 85 hay had a higher CCW (17.41 kg) compared to those fed corn silage (13.66 kg). The average CCW value of the animals evaluated in this experiment was 15.49 kg, similar to the 14.85 kg reported by Pinto et al (2011), who analyzed the inclusion of spineless cactus in the Santa Inês sheep diet. Carcasses with higher CCW were also the better conformed (p < 0.05), these findings corroborate data of Oliveira et al (2018) in Santa Inês lambs at two slaughter ages.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Lambs receiving spineless cactus combined with Tifton 85 hay had a higher CCW (17.41 kg) compared to those fed corn silage (13.66 kg). The average CCW value of the animals evaluated in this experiment was 15.49 kg, similar to the 14.85 kg reported by Pinto et al (2011), who analyzed the inclusion of spineless cactus in the Santa Inês sheep diet. Carcasses with higher CCW were also the better conformed (p < 0.05), these findings corroborate data of Oliveira et al (2018) in Santa Inês lambs at two slaughter ages.…”
Section: Resultssupporting
confidence: 85%
“…Except for chest width, larger (p < 0.05) in animals fed CT compared to CT, the body measurements of sheep were similar between treatments. Pinto et al (2011) reported no effect for the addition of spineless cactus on the body measurements of Santa Inês sheep. Probably, the proximity (p > 0.05) in the values of slaughter weight of the animals subjected to the treatments contributed to the homogeneity in the linear measurements of body circumference of the animals.…”
Section: Resultsmentioning
confidence: 96%
“…The average bunchada weights was 3.22 kg and the yield 13.25%. Medeiros et al (2008) and Pinto et al (2011) observed buchada weights for sheep of the Morada Nova and Santa Inês breeds of 4.72 kg and 5.84 kg and yields of 15.26% and 17.70%, respectively; these values are larger than those found in this study. Clementino et al (2007), evaluating concentrate levels in the sheep diet, obtained buchada weights of 3.36 kg and a yield of 15%, while the panelada weights was 5.81 kg with a yield of 24.06%.…”
Section: Resultscontrasting
confidence: 85%
“…The LEA is used to estimate the amount of muscle in the carcass due to its high correlation with muscle content. Ttherefore, the absence of alteration in the LEA can be considered positive when working with diets containing by-product, because the cost with feeding is reduced without altering the performance of the animals (Pinto et al, 2011). Subcutaneous fat thickness measured above the longissimus dorsi muscle is highly correlated with total carcass fat percentage.…”
Section: Resultsmentioning
confidence: 99%